Water Quality Assessment of a Hydro-Agricultural Reservoir in a Mediterranean Region (Case Study—Lage Reservoir in Southern Portugal) - Catarino, Adriana (2024)
Funding Information: This work was co-financed by the European Union through the European Regional Development Fund, under COMPETE 2020 (Competitiveness and Internationalization of the Operational Program) through the project through the Institute of Earth Sciences projects (ICT; UIDB/04683/2020) with the reference POCI-01-0145-FEDER-007690 and by the European Agricultural Fund for Rural Development through the FitoFarmGest Operational Group (PDR2020-101-030926). This work is part of Adriana Catarino’s PhD with the grant 2023.04004.BD. Publisher Copyright: © 2024 by the authors.